2017
DOI: 10.1002/stem.2710
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Fate of Human Fetal Liver Progenitor Cells Transplanted in Injured Mouse Livers

Abstract: Liver progenitor cells have the potential to repair and regenerate a diseased liver. The success of any translational efforts, however, hinges on thorough understanding of the fate of these cells after transplant, especially in terms of long-term safety and efficacy. Here, we report transplantation of a liver progenitor population isolated from human fetal livers into immunepermissive mice with follow-up up to 36 weeks after transplant. We found that human progenitor cells engraft and differentiate into functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Epithelial cells isolated from foetal human livers have been transplanted into injured murine livers, promoting fibrosis resolution and functionally regenerating parenchyma. 64,65 Comparisons between the matched repopulation capacity of foetal and adult hepatocytes in immune-deficient liver repopulation mouse models have demonstrated superior repopulation capacity of adult over foetal hepatocytes, 66,67 which may be a result of the adult liver providing inadequate signals to retain or promote proliferation of immature cell types. Compared to injecting cells in suspension, which lowers engraftment efficacy (as cells migrate to ectopic sites), direct intrahepatic injection of cells within a hyaluronan matrix significantly improves liver engraftment.…”
Section: Alternative Sources Of Hepatocytesmentioning
confidence: 99%
“…Epithelial cells isolated from foetal human livers have been transplanted into injured murine livers, promoting fibrosis resolution and functionally regenerating parenchyma. 64,65 Comparisons between the matched repopulation capacity of foetal and adult hepatocytes in immune-deficient liver repopulation mouse models have demonstrated superior repopulation capacity of adult over foetal hepatocytes, 66,67 which may be a result of the adult liver providing inadequate signals to retain or promote proliferation of immature cell types. Compared to injecting cells in suspension, which lowers engraftment efficacy (as cells migrate to ectopic sites), direct intrahepatic injection of cells within a hyaluronan matrix significantly improves liver engraftment.…”
Section: Alternative Sources Of Hepatocytesmentioning
confidence: 99%
“…Although less mature cells are believed to engraft and repopulate a host liver less efficiently than mature hepatocytes [16,42,44,45], progenitors have been proven to be useful for transplantations. This has been demonstrated not only in animal models (both single [16,42,45,51] and serial transplantations [44] in transgene-induced liver damage mouse models; in general also treated with Futhan, anti-asialo GM1 or oncostatin M (OSM) to increase efficiency), but also clinically. Sokal et al transplanted 9 × 10 8 adult mesenchymal-like liver progenitor cells (0.75% of total body mass) in a 3-year-old female patient with ornithine carbamoyltransferase (OTC) deficiency, via a percutaneous intraportal catheter.…”
Section: Liver Progenitor Cellsmentioning
confidence: 96%
“…Moreover, it has been suggested that FLPs can also transdifferentiate into functional human endothelial cells with no evidence of neoplasia observed within nine months after transplantation. However, the contamination by endothelial cells in the transplanted LFP cell population was not formally excluded [88]. Being less apoptotic and immunogenic than adult hepatocytes, their smaller size allows for an easier intraportal injection and dispersion compared with primary cells [89].…”
Section: Fetal Liver Progenitors (Flps)mentioning
confidence: 99%